Development of Komarah Comic Media for Anger Management in Adolescents - Najwa Nadhira Harahap; Nefi Darmayanti (Indonesian Journal of Guidance and Counseling: Theory and Application, 2026)
This study aims to develop emotional intelligence-based comic media as a support for guidance and counseling services in helping adolescents manage anger. This study uses the Research and Development (R&D) method with a modified 4D model into three stages: define, design, and develop. The research subjects consisted of two validators (material experts and media experts), 20 seventh-grade students as trial respondents, and one guidance and counseling teacher as the media user. The results showed that the developed comic media had a high level of feasibility, with validation results from media experts of 94% and from material experts of 90%. In addition, the results of limited trials with students obtained a percentage of 89.3% and responses from guidance and counseling teachers of 96.6%, indicating that the media is easy to use, interesting, and well-received by users. Based on these findings, it can be concluded that the developed emotional intelligence-based comic media meets the criteria for validity and practicality as a supporting medium in guidance and counseling services, especially in helping adolescents understand and manage anger. However, this study has not tested the effectiveness of the media experimentally, so further research is needed to examine the effect of media use on changes in adolescent behavior.